Effect of mechanical load cycling on the microleakage of three different glass ionomer restorations in class V cavities - Baharan Ranjbar Omidi; Ladan Madani; Aida Mirnejad Joybari; Ensyeh Rashvand; Sonia Oveisi (Tehran University of Medical Sciences, 2015)
Background and Aims: Microleakage is an important problem with direct restorations and familiarity with contributing factors is of utmost importance. The aim of this study was to evaluate the microleakage of three glass ionomer restorations in class V cavities.   Materials and Methods: In this in vitro study, class V cavity preparations were made on the buccal and lingual/ palatal surfaces of 30 human premolars (60 cavities). The specimens were divided into three group (n=10, 20 cavities). Restored as follows: group1: with Fuji IX (HVGI) ionomer/G coat plus, group 2: Ionofil molar (HVGI)/ G coat plus, and group 3: Fuji II LC (RMGI) / G coat plus. All specimens were finished and polished immediately and were thermocycled (2000 cycles, 5-50°C) . In each group; half of the teeth were load cycled (50000 cycles). Finally, the teeth were immersed in 0.15% basic fushine dye for 24 hours at room temperature and then sectioned and observed under stereomicroscope. Data were analyzed using Kruskal-Wallis, Man- Whitney test and a comparison between incisal and gingival microleakage was made using Wilcoxon analysis.   Results: It was shown that the mechanical load cycling and filling material did not cause a statistically significant increase in the incisal and gingival microleakage in any of groups (P>0.05).   Conclusion: It was concluded that the extent microleakage of Fuji II LC was similar to that of the highly viscous glass ionomers (Ionofil molar, Fuji IX) and load cycling did not increase the microleakage.